The 1984 Peruvian Civil Code: Its elaboration, contributions and the amendments it requires - Fernández Sessarego, Carlos (2014)
In 1965 a Reforming Committee, formed by the leading specialist teachers in each of the books of the Civil Code, was created forreviewing  the  Peruvian  Civil  Code of 1936. After about twenty years, the effort of thehard work of the committee resulted in the enactment of the 1984 Civil Code, which we currently use and know.In this article, the author shares his experience as a legislator, emphasizing new and important aspects included in the Civil Code of 1984. He also proposes possible amendments to the First Book of the current Civil Code, such as the incorporation of standards related to Genetics, a comprehensive review of the subject related to legal capacity, reviewing the subject regarding foundations, among others.